DEVELOPMENT OF COGNITIVE IDEOLOGICAL RESISTANCE IN YOUTH THROUGH NATIONAL EDUCATION IN THE CONDITIONS OF NEURODIGITAL CIVILIZATION (Universal International Scientific Journal, 2026)
In the context of a neuro-digital civilization, where a powerful flow ofinformation, digital technologies, and global ideological influences increasingly affect theconsciousness of young people, the role and significance of national upbringing are analyzed. Themain objective of this research is to identify effective mechanisms for developing cognitive andideological resilience among youth based on national values, traditions, and spiritual heritage.Kalit soʻzlar: kognitiv rezistentlik, mafkuraviy immunitet, axborot xavfsizligi, raqamlimadaniyat, tanqidiy fikrlash ko‘nikmalari, yoshlar ijtimoiylashuvi.
Keywords: cognitive resistance; ideological immunity; information security